The Greek-Swedish-Danish Excavations 2013: A short preliminary report - Hallager, Erik; Andreadaki-Vlazaki, Maria (Proceedings of the Danish Institute at Athens, 2017)
In 2013 the Greek-Swedish-Danish Excavations continued with the main aim to explore the large building of the LM IIA:2/IIIB period, where Linear B tablets were found in situ in 1990. The stratigraphic periods revealed interesting results. From the Venetian cathedral several tombs were excavated. The cathedral was built over an Early Christian Basilica which could be conjecturally reconstructed in ground plan. The Geometric period produced an industrial area, while the LM IIIC period revealed remains of four large rooms – all with fire places. The LM IIIB:2 period was not represented with architecture, but with fine remains of pottery and small finds from a large open area. The large LM IIIA:2/IIIB building revealed remains from five rooms, A spectacular find came from one of these rooms: a decorated pithos intentionally placed on its side and used as a storeroom for, among others, stone tools, fine pottery, fragments of ivory and an unbaked un-inscribed clay tablet.